The South African equity risk premium, country risk and macroeconomic factors - Vlachos, Hermina Gina (My University, 2014)
The equity risk premium is a central parameter in the investment decision making process. As both companies and investors are becoming increasingly entangled in the global economy, they are confronted with the influence of globalisation on the equity risk premium. This research study estimates the South African equity risk premium using the methodology proposed by Fama and French (2002) and further separates the equity risk premium into a global risk premium and a South African country risk premium. The study estimates monthly equity risk, global risk and country risk premiums over the 1980 to 2013 time horizon. The study further investigates the relationship between the country risk premium and macroeconomic fundamentals. This investigation is framed within the confines of the Arbitrage Pricing Theory (APT) framework. The relationship between the country risk premium and the macroeconomic environment is of particular interest to investors, as an understanding of this relationship holds potential risk mitigating and profit yielding opportunities. Multivariate Cointegration techniques and a Vector Error Correction model (VECM) are used to investigate the relationship between the country risk premium and the South African macroeconomic environment. The results of this study provide evidence of a significant long-run relationship between the South African country risk premium and the South African macroeconomic environment. Further, the model estimated by this study can be used to estimate future country risk premiums. Therefore, investors can use the estimated model in the investment decision making process to improve profits in the long-term.
Keywords: Johannesburg Stock Exchange , Investments -- South Africa